2020
DOI: 10.1158/1078-0432.ccr-20-1457
|View full text |Cite
|
Sign up to set email alerts
|

CD19-specific CAR T Cells that Express a PD-1/CD28 Chimeric Switch-Receptor are Effective in Patients with PD-L1–positive B-Cell Lymphoma

Abstract: Purpose: CD19-specific chimeric antigen receptor (CAR) T-cell therapy is effective against refractory or relapsed (R/R) B-cell lymphoma, but the efficacy is hindered by the existence of PD-1/PD-L1 pathway. Patients and Methods: Here, we generated a novel anti-CD19 CAR-expressing PD-1/CD28 chimeric switch-receptor (CD19-PD-1/CD28-CAR). We then conducted a phase Ib study to evaluate safety and efficacy of CD19-PD-1/CD28-CAR T c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 42 publications
0
81
0
Order By: Relevance
“…Recently, we have reported that CD19-PD-1/CD28-CAR T cells exhibited a superior capability of killing PD-L1 + B-cell lymphoma cells in vitro and in vivo relative to the prototype, CD19-CAR T cells. We also demonstrated that this therapy had a favorable safety profile and induced durable clinical responses in the patients with PD-L1 + R/R DLBCL [6]. An interesting aspect of the current study was that CD19-PD-1/CD28-CAR T was generally well-tolerated and resulted in a high response rate that was durable in R/R large B-cell lymphoma after failure of CD19-CAR T therapy.…”
mentioning
confidence: 55%
“…Recently, we have reported that CD19-PD-1/CD28-CAR T cells exhibited a superior capability of killing PD-L1 + B-cell lymphoma cells in vitro and in vivo relative to the prototype, CD19-CAR T cells. We also demonstrated that this therapy had a favorable safety profile and induced durable clinical responses in the patients with PD-L1 + R/R DLBCL [6]. An interesting aspect of the current study was that CD19-PD-1/CD28-CAR T was generally well-tolerated and resulted in a high response rate that was durable in R/R large B-cell lymphoma after failure of CD19-CAR T therapy.…”
mentioning
confidence: 55%
“…A phase Ib study involving patients with PD-L1 + large B-cell lymphoma demonstrated that the ORR of CD19-PD-1/ CD28-CAR T-cell therapy was 58.8%, and that the CR was 41.2%. No severe cytokine release syndrome or neurologic toxicity was reported in that study (17). One recent study reported that high levels of plasma-soluble PD-L1 and signal transducer and activator of transcription (STAT) 3 were related to worse progression-free survival and overall survival in patients with DLBCL (30).…”
Section: Pd-l1mentioning
confidence: 76%
“…A phase Ib study involving patients with PD-L1+ large B-cell lymphoma demonstrated that the ORR of CD19-PD-1/CD28-CAR T-cell therapy was 58.8%, and that the CR was 41.2%. No severe cytokine release syndrome or neurologic toxicity was reported in that study ( 17 ).…”
Section: Pd-l1mentioning
confidence: 81%
“…Our review of the literature, as summarised here, suggests other chemokine pathways that may also be re-purposed to drive CAR-T cell migration and activity, such as the CCL2/CCR2 pathway. CAR-T cells with switch-signalling receptors offer a novel way to convert T cell inhibitory signals, such as those provided by PD1 [ 227 ] to activation signals such as CD28, and a similar process could potentially be used to reverse the inhibitory capacity of glioblastoma-abundant cytokines such as TGF-β, an idea which has been reviewed recently [ 228 ]. An early preclinical study of CAR-T cells with a decoy receptor for TGF-β (a non-signalling ectodomain of the TGF receptor II) prolonged the life of U87 glioblastoma bearing mice and polarized GAM towards an M1 phenotype [ 229 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%